Payment of gratuity act,1972 - Roy, S.R. (Calcutta, 1990)
THE PAYMENT OF GRATUITY ACT, 1972 is a social-welfare legislation and has been enacted to introduce a scheme for payment of gratuity for certain industrial and commercial establishments. In bringing the Act on the statute book the intention of the Legislature was not only to achieve uniformity and reasonable degree of certainty, but also to create and bring into force a self contained, all-embracing, complete and comprehensive Code relating to gratuity. Its significance lies in the acceptance of the principle of gratuity as a compulsory statutory retrial benefit as distinguished from a gracious gift.
Keywords: Payment of gratuity act-Kerala